Hydrogenation via a low energy mechanochemical approach: the MgB2 case. (9th August 2021) - Pistidda, Claudio; Santhosh, Archa; Jerabek, Paul; Shang, Yuanyuan; Girella, Alessandro; Milanese, Chiara; Dore, Maria; Garroni, Sebastiano; Bordignon, Simone; Chierotti, Michele R; Klassen, Thomas; Dornheim, Martin
Abstract: This work aims at investigating the effect that the energy transferred during particle collisions in a milling process entails on solid-gas reactions. For this purpose, the synthesis of Mg(BH4 )2 from MgB2 in a pressurized hydrogen atmosphere was chosen as a model reaction. MgB2 was milled under a broad set of milling parameters (i.e. milling times and rotation regimes) and the obtained product thoroughly characterized. By proving the partial formation of Mg(BH4 )2, the results of this investigation indicate that the energy transferred to the powder bed by the powder particles during milling is not negligible, in particular when the milling process is protracted for a long period.